Electroinduced drift of solvated ions in salt solution of Ce and Ni; Journal of Chemical Sciences; Vol. 130, iss. 8 - Li H. Hongda; Fomin E. S. Eduard Stanislavovich; Kazaryan M. A. Mishik Ayrazatovich; Shamanin I. V. Igor Vladimirovich; Timchenko S. N. Sergey Nikolaevich; Ushakov I. A. Ivan Alekseevich (2018, 2018)
Title screen